Pendistribusian Zakat unto Ormas Islam - Azwar, Zainal (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This paper is motivated by the phenomenon of the temporary closing of????ices of the Council of Ulama of Indonesia of West Sumatra some time ago as a result of the absence of of????ice operational funds. In fact, the role and function of this institution is needed by the community at any time. One of the most stable sources of Islamic economics to fund the activities of these mass organizations is zakat. The problem is whether MUI Islamic organizations are entitled to zakat funds? To answer this question, a literature study was conducted using the Jurisprudence and Jurisprudence Principles. Based on the study conducted, Islamic Society MUI is entitled to zakat funds by compare it to army in the????ield of battle based on illat both aimed to uphold the religion of Allah SWT. The ijtihad model used is ijtihad tathbîqî.